Wilhelm Reich et la politique de l’homosexualité dans le mouvement Sex-Pol - Cat Moir (Cahiers d’histoire)
The Sex-Pol movement (Sexualpolitik) was founded in 1927 in Vienna by Wilhelm Reich. A Communist politicized by the July Revolt of 1927 in Vienna, Reich—a biologist and psychoanalyst by training—believed that political violence resulted from the repression of sexual appetites. According to Reich, sexual repression was one of the main causes of reactionary politics. Sexual liberation was therefore not so much an end of the communist movement as a means to achieve a more just and less violent society. In this context, during the 1930s the Sex-Pol movement saw sexual morality as a real weapon in the fight against fascism. But Reich’s work also reveals contradictions in the sexual morality of communism and the labour movement in the interwar period, especially on the issue of homosexuality. For Reich, homosexuality was a diversion of « normal » sexual energy associated with repressed personalities apt to be seduced by authoritarian tendencies.